READING, PREPROCESSING OF ACCELERATIONS AND CORNERS INCLINATION WITH MPU-6050 I RECORD THEM ON SD-CARD THE ARDUINO DUE - V. G. Mikhailov (Системный анализ и прикладная информатика)
The short review of microcontrollers of family Arduino, their characteristics and application fields is given. Importance of record of parameters of researched object is marked to produce debugging of control systems on microcontrollers Arduino. Unique possibility of registration of parameters in family Arduino is record on SD a card in an alpha mode with usage of functions print (), write (). The problems connected to record of the binary data on SD a card on microcontroller Arduino Due are considered. The analysis of methods of record of the binary data on SD-card Arduino Due, originating problems with neocleaning of memory from the previous program leading to possibility of duplication of the data on SD to a card, presence of the erratic point of view about restriction of volumes of data record and necessity of usage become outdated SD-cards is carried out. Ways of elimination of the marked lacks are considered. The estimation of high-speed performance of various approaches of a data recording on SD a card is led. On the basis of the led researches the approach of multiplexing of the writeable information at the expense of conversion of the binary data is offered is byte-serial in a character array in code ASCI without magnification of their volume and record by units on 240 byte. It allows to use as much as possible standard function possibilities write () Arduino and specificity of the organization of memory SD of cards and to increase high-speed performance more than in 1100 times in comparison with record in a character type on one byte.It is marked that usage of decisions of an exception of duplication of the data offered at forums does not provide completeness of their elimination. For Arduino Due for storage cleaning it is necessary usages of the special programmator or setting of the new program of loading.